Empyema caused by Fusobacterium nucleatum with squamous cell carcinoma of the lung: a case report and literature review - Sun, Yue; Dong, Han; Zhang, Na; Zhao, Peng; Qi, Yuan; Yang, Xin; Wang, Lingling (Frontiers in Medicine, 2023)
Background: Fusobacterium nucleatum is a common oral symbiotic flora that can cause respiratory tract, oral nervous system, obstetric and skin infections. Fusobacterium nucleatum infections are mostly caused by aspiration. The clinical manifestations of pulmonary infections with Fusobacterium nucleatum can include simple pneumonia, lung abscesses, empyema, etc. Case presentation: We described the case of a 49-year-old man with a 1-year history of intermittent cough and sputum production who had worsened over the last 4 days with fever and right chest pain. After thoracentesis and catheter drainage were performed, Fusobacterium nucleatum was detected in the pleural effusion by using next-generation sequencing. Meanwhile, a diagnosis of squamous cell carcinoma of the right lung was made by fiberoptic bronchoscopy. The patient’s condition improved significantly after percutaneous drainage and long-term intravenous antibiotic treatment. Conclusions: This is the first case reported of empyema due to Fusobacterium nucleatum infection in a patient with squamous cell carcinoma.